The art of policymaking : tools, techniques and processes in the modern executive branch - Shambaugh, George E., 1963-; Weinstein, Paul J. (Washington D.C. : CQ Press, 2016)
The Art of Policymaking: Tools, Techniques and Processes in the Modern Executive Branch, Second Edition is a practical introduction to the specific tools, techniques, and processes used to create policy in the executive branch of the U.S. government. George E. Shambaugh, IV and Paul Weinstein, Jr. explain how government officials develop policy, manage the policymaking process, and communicate those policies to stakeholders and the public at large. The authors draw on both their academic and government experience to provide real-world advice on writing policy decision memos, preparing polling questions, and navigating the clearance process. An abundance of case studies show how actual policies are developed and how and why policies and processes differ across administrations. Finally, practice scenarios allow students to apply the tools and techniques they have learned by working through both domestic and foreign policy situations.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Political planning -- United States